Risk Factors for Hock Lesions Occurrence in Dairy Cows - Toncho Penev; Ivaylo Marinov; Dimo Dimov; Zhivka Gergovska; Chonka Miteva; Jurii Mitev (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2019)
The aim of the study was to investigate the risk factors for formation of hock lesions in dairy cattle farms with different housing system. The study included 508 Black‑and‑white Holstein‑type cows from 14 dairy farms in different regions of Bulgaria. On cows a hock lesion assessment (scale 1 to 3) and body condition scoring (scale 1 to 5) were made. From the total number of cows, 231 cows (45.5 %) with score of 2 and 3 were reported, which clinical manifestation was from loss of hairs on the hock joint surface to swellings and wounds. A statistically significant effect of lactation period, body condition scores (BCS) and housing system on the hock assessment score was found. The least square means (LSM) for hock assessment score increased with the advancing of lactation period from 1.22 in cows to 60 days in milk (DIM) to 1.52 in cows after 120 DIM. The percentage of cows with BCS 3 and 3.5 was lower 1.5 to 2 times compared to cows with BCS 1.5. With the lowest mean hock assessment score (1.14), were the cows housed free group on a thick bedding. Tie‑stall housing system occupied an intermediate position with respect to hock assessment, only 1.4 % of cows were with a score of 3. The highest percentage of cows with varying degrees of hock lesions were reported in free‑stall housing system with using of rubber mats for stall floors, 75.5 % of the cows were with hock lesion assessment score 2 and 3. This percentage was slightly lower when small amounts of straw were placed on the rubber mats.